The Concept of voice in Turkish and an analysis of Yunus Emre’s Divan in terms of voice - Ahmet Turan; Elif (Uluslararası Türk Lehçe Araştırmaları Dergisi)
Yunus Emre is one of the important poets in terms of reflecting the language of his time in his poems, making him significant for Turkish language and literature. His works are among the first written texts based on Oghuz Turkish. There are very few surviving works from the Anatolian Seljuk period. Therefore, Yunus Emre's works are also important for reflecting the language, lifestyle and Islam of his era through poetry. For this reason, numerous studies have been conducted on him and his works. Some of these studies focus on grammar. His works have been examined in terms of general grammatical features, as well as specific grammatical categories. In this study, the Divan of Yunus Emre is examined in terms of voice, which is a topic in grammar. Although voice, one of the important subjects in Turkish grammar, has been analyzed by many researchers, a common evaluation method has not yet been reached. In this study, various approaches to the concept of voice are first reviewed, and then an evaluation template is developed within the framework of grammatical criteria. Thus, based on what the predicate requires, an evaluation of voice is made by taking the sentence structure as the basis. In line with the established evaluation template, the first one hundred poems in Yunus Emre's Divan are analyzed. The results obtained from the analyzed poems are exemplified under relevant headings. Additionally, it is taken into account that voice suffixes do not always serve a voice-related function within the sentence. Therefore, the meaning of the predicate containing the voice suffix is also evaluated within the context of the sentence.